Radionuclides in soil around the Rocky Flats environmental technology site, Jefferson County, Colorado - Hulse, Scott E., author; Ibrahim, Shawki, advisor; Borak, Thomas B., committee member; Chapman, Phillip L., committee member; Johnson, Janet A., committee member; Whicker, F. W., committee member (Colorado State University. Libraries, 2002)
Plutonium was released into the environment around Rocky Flats during routine operations, several building fires and remediation efforts at the 903 Barrel Storage Area after barrels containing contaminated oil leaked onto the soil surface. Soil concentrations of naturally occurring and anthropogenic radionuclides were therefore characterized. Mean soil concentrations of naturally occurring 232Th, 40K and 226Ra were 96 Bq kg-1, 720 Bq kg-1 and 63 Bq kg-1, respectively, around Rocky Flats and along Colorado's front range corridor. Rocky Flats is along regional concentration gradients that decrease at a mean rate of 4 Bq kg-1 km-1 for 40K and 0.4 Bq kg-1 km-1 for 232Th from Colorado Springs north to Fort Collins, CO. Variability in soil concentrations of 232Th, 226Ra and 40K is related to soil type, unconsolidated surficial deposits of alluvium and other debris and bedrock. Surface soil concentrations in the top 3 cm of soil and depositions of 241Am decreased in an easterly direction from more than 5.3 kBq kg-1 and 170 kBq m-2 respectively near the 903 pad to 1.3 Bq kg-1 and 0.8 + 0.7 kBq m-2 at distances more than 7 km from the 903 pad at Rocky Flats. Surface deposits of 137Cs from global fallout in the top 3 cm of soil and depositions averaged 0.12 kBq kg-1 and 4.7 kBq m-2 respectively. These deposits were unevenly distributed around Rocky Flats and at regional background locations. Deviations from the uniform exponential rate at which soil concentrations of 137Cs typically decreased with depth, -0.25 cm-1 at undisturbed sites, enabled us to determine that about 10% of sample sites had been disturbed by erosion, tillage or other factors. Soil concentrations of 241 Am decreased with depth at a similar mean rate of -0.22 cm-1 close to the 903 pad where measurements were robust. The mean rate at which 239,240Pu decreased with depth throughout the study area was about the same, -0.23 cm-1. The ratio between soil depositions of 239,240Pu determined using radiochemical analyses and 241Am determined in-situ for locations' close to the 903 pad was 5.4, which is about the same as the ratio of 5.5 between soil concentrations of 239,240Pu and 241Am in the top 3 cm of soil that was estimated from laboratory analyses.
Keywords: environmental science; biogeochemistry